UZBEKISTAN AND ITS ACHIEVEMENTS DURING THE PERIOD OF INDEPENDENCE (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
This article covers the achievements and successes of Uzbekistan during the years of independence. After independence, the country has achieved rapid development in the economy, politics, culture and social spheres. The article provides information about the reforms implemented by the Uzbek government, achieving economic stability, improving the living standards of the population, changes at the national and international levels, and achievements in foreign policy. In addition, the article examines Uzbekistan's international cooperation, attracting investments, progress in education and science, as well as its successes in preserving and developing cultural heritage. These achievements serve to strengthen the republic's position in the international arena.